Superiority of Peremptory Norms in Public International Law - Mahdi , Mahdi; Almaliky, Hadi (Journal of Legal Sciences, 2023)
International law has proven that it is an evolving and flexible law over the years, and despite that, this development takes a very long time, as the concept of peremptory norms took 83 years to crystallize and have concrete and impactful applications, and within this development another modern concept emerged, which is the obligations Erga Omnes in the Barcelona Traction case 1970. We have concluded that these two concepts fall under a broader concept, which is peremptory norms, and this concept represents the common supreme interests of the international community, and consists of rules that transcend all other rules in international law, and it is not permissible to derogate or deviate from them. On the other hand, it bears the obligation of enforcement on all states in the international community.